The Role of Motivation in Mediating the Effect of Competence and Leadership on Employee Performance in Outpatient Poly Installation of Wing Amerta RSUP Sanglah Denpasar - Eka Suardika (Jurnal Ekonomi & Bisnis JAGADITHA, 2020)
Performance is the performance of work or output (output) both quality and quantity. The purpose of this study is to analyze the role of motivation in mediating the influence of competence and leadership on the employee performance of Wing Amerta Installation Sanglah Denpasar Hospital, the respondents are all 50 outpatient personnel, the data collected related to competence, leadership, motivation and performance. Analyzer used in this research PLS (Partial Least Square). The result of this research has positive and significant influence on motivation, leadership has positive influence on motivation and significance, positive competence to performance, and the relationship is significant, competence has positive effect on motivation and relationship is significant, motivation has positive effect on performance and relationship is significant, motivation is partial mediation between Competence to performance, and motivation is the perfect mediation between Leadership on performance